2022
DOI: 10.1097/shk.0000000000001988
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Time to Emergency Department Resuscitative Aortic Occlusion After Noncompressible Torso Hemorrhage

Abstract: Introduction: Time is an essential element in outcomes of trauma patients. The relationship of time to treatment in management of noncompressible torso hemorrhage (NCTH) with resuscitative endovascular balloon occlusion of the aorta (REBOA) or resuscitative thoracotomy (RT) has not been previously described. We hypothesized that shorter times to intervention would reduce mortality. Methods: A review of the Aortic Occlusion for Resuscitation in Trauma and Acute Care Surgery registry from 2013 to 2022 was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…A trauma surgeon is uncommon in Japan, and a surgeon who can provide hemostatic surgery is not always available in many emergency hospitals [14,15]. In addition, because immediate hemostatic surgery is often di cult, the use of bridging measures, such as VA-ECMO or REBOA, is more common in Japan than in the USA [16][17][18][19]. This describes the current characteristics of trauma care in Japan and how they differ from the global standard.…”
Section: Discussionmentioning
confidence: 99%
“…A trauma surgeon is uncommon in Japan, and a surgeon who can provide hemostatic surgery is not always available in many emergency hospitals [14,15]. In addition, because immediate hemostatic surgery is often di cult, the use of bridging measures, such as VA-ECMO or REBOA, is more common in Japan than in the USA [16][17][18][19]. This describes the current characteristics of trauma care in Japan and how they differ from the global standard.…”
Section: Discussionmentioning
confidence: 99%
“…[ 30 ] More recent studies have shown that rapid in-hospital intervention is often insufficient to compensate for severe exsanguination and hypovolemia that occurs before emergency department presentation. [ 31 ] Therefore, prehospital REBOA could be a feasible intervention for a significant portion of severely ill patients in a civilian setting; however, the evidence is limited. [ 28 ] Partial REBOA is currently discussed in preclinical studies, [ 29 ] but has not yet been fully validated.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite this approach and various efforts to reduce prehospital time intervals, response intervals and trauma mortality have largely remained unchanged across the United States over the past decade 5,7 . Given the existing uncertainty around the practicality and benefits of further reducing prehospital response intervals, 7,8 it is imperative to explore alternative strategies to improve patient outcomes. One emerging approach is the application of remote damage control and hemostatic volume replacement procedures closer to the point of injury with prehospital blood transfusion (PHBT) programs 9 .…”
mentioning
confidence: 99%